UPI: A Brilliant Technology Idea Executed Poorly (Trinity Journal of Management, IT & Media (TJMITM), 2017)
online banking and mobile commerce. So in our developing  economy, people also need a less complex and secure mode of  payments and mobile banking.  According to reports published by Business Standard [1],  cashless payments in October 2016 increased 22%, when Till a few years ago, nobody imagined that mobile phones would  be used to transfer money and complete shopping transactions.  But now, one doesn't really have to visit a bank, stop by at an  ATM, or carry a plastic credit or debit card to make purchases.  Mobile banking through mobile apps now days are on boom. The  continuous increase in mobile banking users is due to  technological advancements which has restored and increase  the faith of users towards mobile banking and different payment  modes. In a developing country like India, where mobile users  are growing at very fast speed, because of the low cost smart  phones and people can also afford that technology, the problems  and complexity will also growing rapidly. Users expectations in  terms of speed, convenience and security are now a days a major  concern. The technologies like NEFT, IMPS, RTGS etc. have  been functioning very well but what next? What is the future of  mobile banking? To make sure that mobile payments stay in the  market in future and it is used by most users, the national  payment corporation of India has initiated a new payment system  called as unified payment interface(UPI) that make online  payments much easier without requiring a digital wallet or credit  or debit card. You either need to know the other's person MMID  (mobile money identifier) or a Virtual Payment Address (VPA)  and phone number. All these features of UPI will surely boost the  confidence of e-commerce and m-commerce customers as they  won't have to go through the hassled process entering the  credit/debit card information every time and also no need of  remembering the bank account numbers, IFSC code and several  pins associated with several bank accounts.
Keywords: Mobile banking; UPI; NPCI; ecommerce; mcommerce; payment